Assessment of Saliva Specimens' Reliability for COVID-19 Surveillance - Pierri, Biancamaria; Tafuro, Maria; Cuomo, Maria Concetta; Concilio, Denise Di; Vassallo, Lucia; Pierri, Andrea; Ferro, Amedeo; Rofrano, Giuseppe; Gallo, Alfonso; Stasio, Antonio Di; Mancusi, Andrea; Galdi, Lydia; et al. (Frontiers in Public Health, 2022)
The aim of the present study is to assess saliva as a reliable specimen for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection by real-time reverse transcription-PCR (RT-PCR), especially in community mass screening programs. The performance analysis considered 1,221 total samples [nasopharyngeal (NP) swabs and corresponding saliva], tested by means of a reference diagnostic real-time RT-PCR assay. Conflicting results were further investigated with a second, more sensitive, reference assay. Analysis of agreement showed a good concordance (95.82%), with a k coefficient value of.74 (p < 0.001); moreover, a follow-up analysis revealed the presence of viral gene targets in saliva samples at the time point the corresponding NP swabs turned negative. Data obtained prove the reliability of this alternative biofluid for SARS-CoV-2 detection in real-time RT-PCR. Considering the role of saliva in the coronavirus disease 2019 (COVID-19) transmission and pathogenesis, and the advantages in the use of salivary diagnostics, the present validation supports the use of saliva as an optimal choice in large-scale population screening and monitoring of the SARS-CoV-2 virus.